The Australian carbon farming initiative: early developments ongoing challenges - Rosano, Michele; Duncan, D. (Otemon Gakuin University, 2012)
This paper reviews the early results of the Carbon Farming Initiative (CFI) within the Australian Federal Government’s recently introduced Carbon Pricing Mechanism (CPM) program. The paper introduces the CPM and its core design elements. It then specifically reviews the CFI domestic offset program and how it fits within the CPM. Discussion then centres on a review of the CFI program in Australia. A brief analysis is then provided on the early achievements of the CFI through a review of a number of currently approved CFI projects. The paper then concludes with a review of the current challenges to the success of these programs in Australia. It is gratefully acknowledged that research funding for this paper was provided under the auspices of Otemon Gakuin University’s Center for Australian Studies.